REVITALISASI KEMANDIRIAN HAKIM MELALUI KONSEP PERADILAN RAMAH SEBAGAI WUJUD OPTIMALISASI AKUNTABILITAS LEMBAGA PERADILAN DI INDONESIA - Ingrit, Ingrit (Ikatan Hakim Indonesia (IKAHI), 2023)
One of the big challenges from the past until now for judicial independence in Indonesia, namely the large number of interventions that come from various parties, both internal and external. This phenomenon illustrates that the current judicial situation is unhealthy, because institutions that should stand by maintaining their independence, are actually weakening due to influences and conflicts that attack the integrity of the judicial institution. This situation certainly raises questions from the public about the demise of Indonesia's judicial independence, which ultimately makes the public lose confidence in the judiciary as a place to seek justice. The judge in this case as a functional body of the implementation of the judiciary, which basically the judicial power is formed and compiled on the basis of legislation. As a law enforcer, the integrity of judges can be seen through their decisions, therefore judges must have freedom and moral values as their authority to decide cases, because the independence of judges is a representation of the state of law. Although various policy measures have been pursued in order to reform the judiciary, without independence or independence in the judicial power body, it will certainly be easier to provide access to opportunities that can affect and adversely affect including paving the way for the emergence of abuse of power or deviation of power and also the neglect of human rights by state rulers.